The Comparison of Anxiety Disorder Among Ex-Female Sex Workers and Non-Female Sex Workers in The Ex-localization Area - Angkawidjaja, Merry Apriliani; Wardhana, Ardyan Prima; Dahliana, Anita (Keluwih: Jurnal Kesehatan dan Kedokteran, 2023)
Abstract—Indonesian localization of Female Sex Workers (FSW) was one of the largest in Southeast Asia, which has been taken by the government since 2014. The impact of mental health disorders has not yet been reported. This study aimed to compare the anxiety disorder among ex-FSW and non-FSW. This was a study to compare the prevalence of anxiety disorders among ex-FSW compared to non-FSW, located in ex-localization in Surabaya, Indonesia. Seventy-five participants met inclusion criteria and were gathered on December 10th, 2022 to complete Beck Anxiety Inventory (BAI) tests. The results showed that 16,67% of participants (n=12) were found with clinical anxiety scores. Among them, 41,67% ex-FSW (n=5) and 58,33% non-FSW (n=7). The prevalence of anxiety disorder, also the total BAI score, compared to the work history of FSWs and non-FSWs were found not associated (p>0.05). The anxiety disorder was found higher in the non-FSW group than ex-FSW group. But there was no difference found in the prevalence of anxiety and the BAI score between ex-FSW and non-FSW. Keywords: anxiety disorder, female sex workers, mental disorders Abstrak—Eks-lokalisasi Pekerja Seks Komersial (PSK) di Indonesia adalah salah satu yang terbesar di Asia Tenggara, yang ditutup pemerintah di tahun 2014. Dampaknya pada kesehatan mental belum pernah dilaporkan. Penelitian ini bertujuan untuk membandingkan gangguan cemas diantara mantan PSK dan non-PSK. Penelitian ini adalah studi untuk membandingkan prevalensi gangguan cemas diantara mantan PSK dan non-PSK sekitar eks-lokalisasi di Surabaya, Indonesia. Didapatkan 75 partisipan yang memenuhi kriteria inklusi, mereka dikumpulkan pada 10 Desember 2022 untuk mengisi tes Beck Anxiety Inventory (BAI). Hasil penelitian menunjukkan bahwa 16,67% partisipan (n=12) didapatkan hasil positif untuk skor kecemasan, di antaranya, 41,67% mantan PSK (n=5) dan 58,33% non-PSK (n=7). Prevalensi kecemasan serta total skor BAI tidak berhubungan dengan riwayat pekerjaan mantan PSK dan non-PSK. Gangguan kecemasan ditemukan lebih tinggi pada non-PSK dibandingkan mantan-PSK. Namun, tidak ditemukan perbedaan prevalensi kecemasan dan skor BAI diantara mantan PSK dan non-PSK. Kata kunci: gangguan cemas, gangguan mental, wanita pekerja seks komersial